Environmental influences on tuna movement patterns in the Indian Ocean - Motah, Beenesh Anand (Department of Oceanography, 2017)
The Indian Ocean Tuna Commission conducted a small-scale tagging programme (2002-2009) and also a large-scale tagging programme: the Regional Tuna Tagging Programme of the Indian Ocean (RTTP-IO, 2005-2009). Both tagging programmes known as the Indian Ocean Tuna Tagging Project (IOTTP), targeted three main species of tuna commercially exploited in the Indian Ocean: bigeye (Thunnus obesus), skipjack (Katsuwonus pelamis) and yellowfin (Thunnus albacares). The two programmes tagged 219,149 tuna and 34,294 recaptures were reported to the commission. This study focused on tuna behaviour in the Indian Ocean looking at seasonal impacts, inter-annual variability in relation to ocean environment, survival estimates, movement patterns, size-groups and school-type: Free Schools (FS) and Fish Aggregating Devices (FADs). Using a multivariate approach, it was found that the years 2005 to 2007 were most abundant in recoveries of skipjack adults (77.45%) while yellowfin adults were mainly abundant during 2008 to 2011. It also showed that year and zone were significant factors influencing local abundance in tuna. The Kaplan-Meier survival curves enabled estimates on the longevity of the three species to be made. It was estimated that the cohorts (99%) vanished at 12, 5.8 and 10 years for bigeye, skipjack and yellowfin, respectively. The years 2006 (cold-productive phase) and 2007 (warmchlorophyll depleted phase) showed tuna movement patterns changing with an El Ni˜no event and primary productivity. Tuna tagged in the Tanzanian region, showed that those under FADs moved pre-dominantly towards the Somalian and Seychelles waters, while those in FS moved to the Seychelles and Mozambique waters. General Additive Model (GAM) analyses showed that the area bounded by 5⁰N-5⁰S and 45⁰-55⁰E was the main tag recovery regions for tuna under FADs. While in FS, the core recovery region was observed to be from 0⁰N-10⁰S and 50⁰-60⁰E. Recoveries were distributed in the temperature range 25-29 ⁰C. Modelling tuna movement and drift related to ocean surface currents and swimming speed, a closer match between simulated and actual recovery positions were obtained for large tuna (particularly free schools) in comparison to small tuna associated with FADs.